Strategic Management of Prophet Lut 'Alaihissalam's Da'wah to the People of Sodom - Utama, Abdul Alimun; Firmansyah, M. Feri (Jurnal Ilmiah Mandala Education (JIME), 2024)
This study aims to determine the strategic management of the da'wah of the Prophet Luth 'alaihissalam in his people, namely the sodomites. The sub-problems of the subject matter are as follows: 1. What is the story of the Strategic Management of the Da'wah of the Prophet Luth 'alaihissalam to his people? 2. How was the cultural acculturation of the habits of the sodomites during the time of Prophet Luth 'alaihissalam? The author uses a type of cultural research using qualitative descriptive data analysis, which is research intended to understand phenomena or events regarding the story of the Prophet Luth 'alaihissalam's da'wah journey. The research approaches used are, Anthropological approach, Religious approach, and historical approach. Furthermore, the method of data collection using Library Riset, the author tries to express the object discussed according to reality that happened to the story of the Prophet Luth. The result of this study is to show that there is a synergy between the steadfastness of Prophet Luth called upon his people to worship Allah only and forbid such heinous acts (homosexuality).